(untitled) (Research, Society and Development, 2022)
Due the reality of the countless cases related to diseases and accidents in the work environment, the need for more responsible attitude on the part of organizations and greater importance to be given in relation to working conditions and worker safety emerges. At the same time, their well-being and professional satisfaction in work environment have become a more strategic theme for achieving transformations and improvements in such an environment. This article addresses this issue, aiming to see the workers’ perception of Work Safety in a thermoplastic industry. The research is classified as applied, with a qualiquantitative approach. Observation scripts and questionnaires were applied to the 100 employees with 20 statements related to the Regulatory Norms relevant to the sector. For statistical treatment and factorial analysis of data, SPSS|Statistics and Excel software were used. It was identified that the company has positive practices that reflect in a healthy environment for employees from the points observed in the Roadmap. This can be confirmed in the first part of the results, the Descriptive Analysis, in which only one statement (S11) indicated a negative perception. In the Factor Analysis, it was noticed that the study presented a post rotation matrix of factors with the values ​​of high factor loadings in the description of each variable. In view of these results, it can be concluded that the company studied has a positive perception in relation to the reflection of safety practices at work, a factor that consequently tends to also influence the performance of workers.